Orthogonal Experimental Study on Multifactor Conditions for Gas Desorption in Coal - Fakai Wang; Yunpei Liang; Xuelong Li; Lei Li; Jianggong Li; Yulong Chen (Advances in Civil Engineering)
The isothermal adsorption experiment of coal is an important method to study the mechanism of coal gas desorption. The orthogonal experiment is used to compare the gas desorption mechanism of coal under multifactor conditions, such as the particle size, temperature, pressure, moisture content, and molding pressure. The sensitivity of five factors was used to conduct regression analysis. The sensitivity and influence degree of five factors on the coal gas desorption capacity were analyzed. The results showed the following: (1) the effect of the coal sample particle size, temperature, pressure, moisture content, and molding pressure of coal on the sensitivity of desorption capacity is shown as C (pressure) > B (temperature) > A (particle size) > D (moisture content) > E (molding pressure); (2) the regression analysis of various factors for gas adsorption indicates that the degree of correlation of the multivariate quadratic regression equation is higher compared to that of the multivariate one-time regression equation; and (3) the coal sample particle size, temperature, pressure, moisture content, and type of gas desorption can well represent the gas desorption capacity of a coal sample under various conditions. The smaller the particle size of the coal sample, the higher the ambient temperature, the higher the gas pressure, the lower the moisture content of the coal sample, and the greater the gas desorption per unit mass in 30 min after coal sample gas adsorption equilibrium. The orthogonal test results have important theoretical significance for guiding gas adsorption and desorption tests of coal. For coal and gas outburst prediction, the coal seam gas flow mechanism, coal gas content prediction, and calculation of the mining coal gas emission have important practical significance for gas explosion accident prevention.